THE MECCAN FATWAS AND THE GLOBALIZED DISCOURSE OF EXCLUSION: THE CASE OF ANTI-AHMADIYAH MOVEMENTS IN INDONESIA - Darmadi, Dadi (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
This article explains the historical and global contextualization of intolerance towards religious minority group such as Ahmadiyah and it analyzes the recent increased animosity towards them in Indonesia. This paper argues that to understand the current persecution of Ahmadiyah one must begin with an examination of the early transnational efforts to marginalize Ahmadiyah and their effects on Muslim Commnunities. The Meccan fatwas in focus and their reproduction ?provide an example of the ways in which such globalized discourses of exclusion regarding a particular religious group were strategically framed and mobilized in i.e. Lahore, Mecca and few other places, and how these historical and theological factors at play could provide more insight into the rising political intolerance and the criminalization of religious views in Indonesia.